A new experimental method to simulate dynamic crevice corrosion in modular hip arthroplasty. (September 2021) - Hornus, Edgar; Wang, Ke; Pabbruwe, Moreica; Kop, Alan; Jones, Chris; Salleh, Ashraf; Salasi, Mobin; Iannuzzi, Mariano
Abstract: A new method was developed to study the complex corrosion mechanism found in modular hip arthroplasty, i.e., dynamic crevice corrosion. Short wear events followed by rest times were applied in a conformal tribocontact to simulate different activity levels. Likewise, stepped potentiostatic polarization testing and electron microscopy were used to compare dynamic (continuous and interrupted) and static conditions. Results showed that 316L stainless steel underwent severe corrosion under the dynamic setting. The findings reproduced the extent and morphology of attack found in a retrieved implant. Thus, the new method could be used to investigate the corrosion susceptibility of modular hip arthroplasty.